Bis(2-methylquinolin-8-olato-kappa N-2,O)lead(II) - Mohammadnezhad, G.; Ghanbarpour, A.R.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Pb-II atom in the title compound, [Pb(C10H8NO)(2)], is chelated by two oxine (2-methylquinolin-8-olate) anions in a psi-trigonal-bipyramidal geometry; the N atoms occupy the axial sites. The molecule lies about a twofold rotation axis.